1997
DOI: 10.1901/jeab.1997.67-337
|View full text |Cite
|
Sign up to set email alerts
|

Running and Responding Reinforced by the Opportunity to Run: Effect of Reinforcer Duration

Abstract: The present study investigated the effect of reinforcer duration on running and on responding reinforced by the opportunity to run. Eleven male Wistar rats responded on levers for the opportunity to run in a running wheel. Opportunities to run were programmed to occur on a tandem fixed-ratio 1 variable-interval 30-s reinforcement schedule. Reinforcer duration varied across conditions from 30 to 120 s. As reinforcer duration increased, the rates of running and lever pressing declined, and latency to lever press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
96
1
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 126 publications
(104 citation statements)
references
References 27 publications
6
96
1
1
Order By: Relevance
“…In the rat, running almost exclusively occurs at night as many other appetitive behaviors (Eikelboom and Mills, 1988). It is generally agreed that wheel running is naturally rewarding and strongly depends on animal motivation to perform this behavior (Belke, 1997;Iversen, 1993;Yu et al, 2005). It has been demonstrated that the pattern of operant responding to gain access to a wheel was similar to those observed for conventionally accepted consummatory reinforces such as food and water (Belke, 1997).…”
Section: Voluntary Running As An Indicator Of Manganese-induced Toxicitymentioning
confidence: 98%
See 1 more Smart Citation
“…In the rat, running almost exclusively occurs at night as many other appetitive behaviors (Eikelboom and Mills, 1988). It is generally agreed that wheel running is naturally rewarding and strongly depends on animal motivation to perform this behavior (Belke, 1997;Iversen, 1993;Yu et al, 2005). It has been demonstrated that the pattern of operant responding to gain access to a wheel was similar to those observed for conventionally accepted consummatory reinforces such as food and water (Belke, 1997).…”
Section: Voluntary Running As An Indicator Of Manganese-induced Toxicitymentioning
confidence: 98%
“…It is generally agreed that wheel running is naturally rewarding and strongly depends on animal motivation to perform this behavior (Belke, 1997;Iversen, 1993;Yu et al, 2005). It has been demonstrated that the pattern of operant responding to gain access to a wheel was similar to those observed for conventionally accepted consummatory reinforces such as food and water (Belke, 1997). Due to a rather complex nature, wheel running is a highly plastic behavior and can be influenced by a variety of internal and external factors that justify its use in many applications.…”
Section: Voluntary Running As An Indicator Of Manganese-induced Toxicitymentioning
confidence: 99%
“…For example, if I asked you why you stopped eating (an ingestive behavior), you would probably say that you were full (satiated; e.g., Bizo et al, 1998). If I asked you why you stopped running (an energetic response), you would probably say that you were tired (fatigued; e.g., Belke, 1997). If I asked you why you stopped studying (a cognitive behavior), you might say that you were bored (your attention waned; e.g., Hinson & Tennison, 1999).…”
Section: Separating Satiation and Habituationmentioning
confidence: 99%
“…Similarly, pairing a distinctive environment with the aftereffects of running produces a conditioned place preference in laboratory animals (Lett et al, 2000;Belke and Wagner, 2005). Exercise can also serve as a positive reinforcer, as both laboratory animals (Iversen, 1993;Belke, 1997;2000;Belke and Dunbar, 2001) and in-patient clinical populations (Schebendach et al, 2007) will perform an operant response that leads to the opportunity to exercise.…”
Section: Introductionmentioning
confidence: 99%